Integrating conservation objectives into forest management: coppice management and forest habitats in Natura 2000 sites - Mairota P; Buckley P; Suchomel C; Heinsoo K; Verheyen K; Hédl R; Terzuolo Pier G; Sindaco R; Carpanelli A (iForest - Biogeosciences and Forestry, 2016)
Most forest habitats, as defined and listed for their nature conservation importance in the Habitats Directive of the European Union and in the Bern Convention, result from centuries of human intervention. This paper explores the scope for, and the attitudes towards coppicing in Natura 2000 sites in some of the EU28 countries where coppice was historically one of the most important traditional silvicultural systems. A questionnaire survey was circulated to experts involved with Natura 2000 sites and case studies were conducted in Belgium, the Czech Republic, Estonia, Germany, Italy and the United Kingdom, to investigate attitudes to coppice silviculture within the framework of Natura 2000 site management plans. A list of forest habitat types capable of being managed as coppices was compiled and populated with sites at national and regional levels. At the regional level, management plans for the relevant forest habitat types in Natura 2000 sites were critically scrutinised together with other statutory, administrative or contractual measures. The results show that approaches to integrate coppice management into conservation plans differ widely. Examples of disparities are given and the possible causes discussed. A case is made for coppicing to be continued, where appropriate, as an important strategy in site management plans that aim to conserve habitats and improve forest biodiversity.